Research of the specific steel shells progressive collapse prevention - Reznik, Рetro; Grebenchuk, Sergiy; Koreniev, Roman; Bondarenko, Vitaliy (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article deals with coatings in the form of the specific steel shells. After a detailed analysis certain number of accidentsand collapses, these collapses can be classified as “progressive” collapse. The main purpose of the article is the developmentof design algorithms for evaluation of the stress-strain state and preventing the progressive collapse of the specific steelshells. The method of prevention progressive collapse has been developed in the form of a constructive modernization.The comparative finite-element analysis of the strained-strain state of the specific shells original models, models of discretecontinualribbed shells (with constructive upgrading) and models of solid ribbed shells has been carried out. From the analysisresults it can be concluded that the proposed modernization method can be considered as one of the possible options forpreventing progressive collapses and increasing the bearing capacity of specific steel shells.
Keywords: steel shell; arched thin-walled profiles; progressive collapse; buckling; open-type cylindrical compound shell